Switching From Glargine to Degludec: The Effect on Metabolic Control and Safety During 1-Year of Real Clinical Practice in Children and Adolescents With Type 1 Diabetes - Predieri, Barbara; Suprani, Tosca; Maltoni, Giulio; Graziani, Vanna; Bruzzi, Patrizia; Zucchini, Stefano; Iughetti, Lorenzo (Frontiers in Endocrinology, 2018)
Background/Objective - Insulin degludec (IDeg) is an ultra-long-acting analogue with less daily variability compared to other basal insulins. In this retrospective study we examined 1-year efficacy and safety of IDeg in youth with type 1 diabetes (T1D). Subjects/Methods: Thirty-seven patients [11.7±4.22 years; T1D duration 4.97±3.63 years; once-daily glargine (IGlar) by at least 1 year] were switched to once-daily IDeg because of glycosylated hemoglobin (HbA1c) >7.5% and/or reported physical pain at IGlar injection. Changes in HbA1c, 30-day mean fasting plasma glucose (mean FPG), daily insulin dose, and severe hypoglycemia rates were collected at basal insulin switch (T0), 3-months (T1), 6-months (T2), and 12-months (T3) after IDeg was started. Results: In patients with HbA1c >7.5% at T0 we found a decrease in HbA1c values (%) from 8.46±0.53 to 7.89±0.72 at T1 (p=0.008) and 7.97±0.89 at T2 (p=0.035). At T3, 38.9% of patients had HbA1c ≤7.5%. Mean FPG levels significantly decreased at T2 (p=0.043). In the overall study population, we documented an increase in IDeg dose (+12.5% at T3; p<0.001) and a decrease in mealtime insulin dose (-11.6% at T3; p=0.001) after switch. HbA1c levels were unchanged. No episode of severe hypoglycemia was reported. Conclusions: Our data in children and adolescents with T1D suggest that IDeg dose should be increased by 12% and mealtime insulin doses should be lowered by 11% for patients who previously received IGlar. IDeg might be considered useful and well tolerated and it seems to improve the glycemic control compared to IGlar, mainly in patients with poor glycemic control.